Active video games: An opportunity for enhanced learning and positive health effects? - Maddison, R.; Simons, M.; Straker, Leon; Witherspoon, L.; Palmeira, A.; Thin, A. (Practical Memory Institute, 2013)
Active video games are an emerging genre of electronic games that provide engaging exercise experiences by combining physical exertion with interactive game play. As such they have attracted increased interest from health promotion professionals to reduce sedentary behavior, increase physical activity, and improve health outcomes such as body composition. However their potential for enhancing the educational experience has not been extensively explored. This paper provides a brief overview of active video game research to date and outlines opportunities for future research. Specifically, we highlight the need to develop a conceptual framework to better understand the determinants, mediators, moderators, and consequences of active video gaming and integrate learning and health outcomes. We propose that active video games can be a key part of a wider “digital” supportive environment where education and health researchers and professionals work with, rather than against, video game technologies to promote learning and health.